Transgender and gender diverse individuals embodying endometriosis: a systematic review - Giacomozzi, Maddalena; Bouwens, Jip; Aubin, Stéphane Guy; Pastoor, Hester; Verdonk, Petra; Nap, Annemiek (Frontiers in Medicine, 2024)
Background Transgender and gender diverse (TGD) people embody social and health inequalities that disproportionately affect this community more than the cisgender population. Endometriosis is a chronic condition of the reproductive tract that affects 5–10% of cisgender women. A recent systematic review with meta-analysis uncovered a pooled prevalence of 25.14% among TGD individuals undergoing gender-affirming surgeries. Objective This study aims to investigate the causes of the gap in prevalence of endometriosis between the TGD community and the cisgender population. Methods A systematic review with a fit-for-framework analysis was conducted. Results were analysed according to the adjusted developmental framework for embodiment with an intersectional approach. Sources were categorised in multi-levels relating to the framework mechanisms of expression, shaping, interaction, and incorporation. Results Four hundred twenty-three (423) studies published between 2001 and 2024 in English and Spanish were identified on the PubMed, Web of Science, Sociological abstracts, and PsycInfo databases. Thirty-two (32) peer-reviewed sources were selected. Discussion The higher prevalence of endometriosis among TGD people compared to the cisgender population reflects a complex phenomenon whereby individual biomedical characteristics, and psychological and environmental factors interplay on multiple levels throughout one’s lifespan. The prevalence gap is striking in a context where TGD people experience great barriers and delays to access healthcare, and endometriosis is typically understood as a “women’s disease.” TGD people express lifestyle and environmental factors correlated with endometriosis more often than cisgender women, such as history of trauma, low self-image, obesity. Endometriosis interacts with one’s quality of life, and especially with gendered expectations related to menstruations, family planning and sexuality. This interference can result in biographical disruption and gender self-perception changes in both cisgender and TGD people. Exogenous testosterone use as gender-affirming therapy results in amenorrhea in 80% of cases. However, endometrium and follicular activities are still reported upon testosterone use suggesting endometriosis may be active. It is hypothesised that testosterone use could lead to a hyper-estrogenic state that would stimulate endometriosis proliferation.